Activation of pyrophosphate:fructose-6-phosphate 1-phosphotransferase by fructose 2,6-bisphosphate stimulates conversion of hexose phosphates to triose phosphates but does not influence accumulation of carbohydrates in phosphate-deficient tobacco cells. - Fernie, A; Roscher, A; Ratcliffe, R; Kruger, N (2002)
The aim of this work was to investigate the contribution of fructose 2,6-bisphosphate to the regulation of carbohydrate metabolism under phosphate stress. The study exploited heterotrophic tobacco callus lines expressing a modified mammalian 6-phosphofructo-2-kinase/fructose 2,6-bisphosphatase that increased the fructose 2,6-bisphosphate content of the tissue. The phosphate status of two transgenic and one untransformed cell line was perturbed by incubation with 2-deoxyglucose, a phosphate-sequestering agent, and by growth of callus on phosphate-depleted media. 31P-NMR spectroscopy confirmed that both treatments decreased cellular levels of inorganic phosphate and phosphorylated metabolites. Despite large decreases in the amounts of phosphate esters, UDPglucose and adenylates in response to phosphate deficiency, the fructose 2,6-bisphosphate content of each line was unaffected by 2-deoxyglucose and increased during growth on phosphate-limited media. Short-term treatment of callus with 2-deoxyglucose had only minor effects on the carbohydrate status of each line, whereas long-term phosphate deficiency caused an increase in starch and a decrease in soluble sugar content in both transgenic and control lines. There were no consistent differences between the three callus lines in metabolism of [U-14C]glucose in response to incubation with 2-deoxyglucose. In contrast, there was a decrease in partitioning of label into glycolytic products (particularly organic acids) in untransformed callus during growth on phosphate-depleted medium. This decrease was greatly attenuated in the transgenic lines with increased fructose 2,6-bisphosphate content. This suggests that the conversion of hexose phosphates to triose phosphates is constrained under phosphate-deficient conditions, and that this restriction can be relieved by activation of pyrophosphate:fructose-6-phosphate 1-phosphotransferase. However, since the transgenic and control lines did not differ in the extent to which the carbohydrate content changed in response to growth on phosphate-depleted media, it is concluded that an increase in flux through pyrophosphate:fructose-6-phosphate 1-phosphotransferase is not a major component of the metabolic response of heterotrophic tobacco cells to phosphate deficiency.